PELATIHAN KEWIRAUSAHAAN DALAM MEMPERSIAPKAN WIRAUSAHA-WIRAUSAHA BARU DI PKBM NURUL QOLBI KOTA BEKASI - JAWA BARAT - Sahroni Sahroni; Edy Krisyanto; Yulian Bayu Ganar; Mukrodi Mukrodi; Mohamad Duddy Dinantara (LPPM Universitas Pamulang, 2020)
On 14,15,16 April 2019, we have successfully carried out community service activities at PKBM NURUL QOLBI located on Jl. Pandu II Ujung No.154, Kelurahan Sepanjang Jaya, Rawa Lumbu District, Bekasi City. The Purpose of Community Service Activities is to carry out the Tri Dharma of Higher Education. Also expected from the results of this activity is that universities can contribute to the development and application of science to the community, especially to NURUL QOLBI PKBM students. The method used in this activity in the form of lectures and questions and answers about human resources, especially for students in order to improve the quality of student human resources through entrepreneurial motivation and knowledge, careers in the world of work, knowledge of education in higher education. The result of community service is the increasing knowledge of PKBM NURUL QOLBI students about entrepreneurship, career and education in higher education. The knowledge gained by students in community service activities is expected to be able to provide motivation and provision of knowledge for students in the future. And also will have a multiplier effect on the economy of the family and the community in their environment.Keywords: Training, Entrepreneurship.